2015
DOI: 10.1002/maco.201508566
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion cracking assessment of API X65 steel non‐conventionally heat treated

Abstract: Stress corrosion cracking (SCC) susceptibility of API X65 steel nonconventionally heat-treated was evaluated through slow strain rate tests (SSRTs) using the synthetic soil solution NS4 at 20, 40 and 60 8C. Polarization curves (PCs) and corrosion potential (E corr ) measurements were also performed. The non-conventional heat treatment (HT) was made by heating plates at 1050 8C for 30 min followed by water quenching. The tensile strength of the heat-treated plates increased to values similar to API X80 steel. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
3
1
0
Order By: Relevance
“…On the other hand, the yield strength (σ YS ) and ultimate tensile strength (σ UTS ) values decreased at pH 8 and pH 10 in comparison with air condition, while at pH 3, this tensile strength increased due to the embrittlement of the material. This increase in σ YS and σ UTS and loss in ductility has been reported by other authors [ 37 , 42 , 43 ], which can be attributed to the hydrogen diffusion into the crystal lattice of metal and interacts with the dislocations and blocks their movement, which produce hardening of the steel. In the acid solution (pH 3), atomic hydrogen is generated by the cathodic reaction of H + protons [ 43 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, the yield strength (σ YS ) and ultimate tensile strength (σ UTS ) values decreased at pH 8 and pH 10 in comparison with air condition, while at pH 3, this tensile strength increased due to the embrittlement of the material. This increase in σ YS and σ UTS and loss in ductility has been reported by other authors [ 37 , 42 , 43 ], which can be attributed to the hydrogen diffusion into the crystal lattice of metal and interacts with the dislocations and blocks their movement, which produce hardening of the steel. In the acid solution (pH 3), atomic hydrogen is generated by the cathodic reaction of H + protons [ 43 ].…”
Section: Resultssupporting
confidence: 81%
“…NS4 solution has the following composition: 0.483 g/L NaHCO 3 , 0.122 g/L KCl, 0.137 g/L CaCl 2 , and 0.131 g/L MgSO 4 7H 2 O. Several studies [ 35 , 36 , 37 ] have used the NS4 solution to simulate the ionic species present in the soil electrolyte.…”
Section: Methodsmentioning
confidence: 99%
“…However, the percentage of strain decreases more than 1 per cent. This increase in mechanical properties in YS and UTS and loss in ductility and elongation have also been observed in others research works (Cheng, 2007a;Quej-Aké et al, 2013;Contreras et al, 2012;Natividad et al, 2016;Velazquez et al, 2009;Contreras et al, 2015;Bueno et al, 2014), whose increase is attributed to the interaction of hydrogen atoms with dislocations, hindering its movement; thus, the steel is hardened, and therefore, there is a decreases in strain, because the dislocations increase the number of sites of hydrogen entrapment (Cheng, 2007a;Torres-Islas et al, 2013;Javidi and Horeh, 2014;. Also is observed that the greater YS produces a smaller plastic area, and this produces lower ductility.…”
Section: Ssrtsupporting
confidence: 88%
“…Others evaluate the effect of cathodic potentials applied (Velazquez et al, 2009;Contreras et al, 2012;He et al, 2004;Choi and Kim, 2009;Contreras et al, 2010), and few works assess the effect of heat treatment applied to steels on the SCC behavior. (Natividad et al, 2016;Gonzalez-Rodriguez et al, 2000;Albarran et al, 1999). In spite of the different test conditions used by the different researchers, the results found are similar reporting that the steels suffer dissolution, hydrogen embrittlement, toughness loss and transgranular fracture type for neutral pH with brittle appearance in many cases.…”
Section: Introductionsupporting
confidence: 69%